Diseños óptimos bayesianos para estimación de parámetros en farmacocinética (2012)
In pharmacology, especially on the pharmacokinetics ﬁeld, the main interest is the study of the drug concentration in the plasma tissue. This area uses nonlinear models given by the particular administration of a medicine. The purpose of bayesian approach is to construct optimal designs restricted to an utility function, to maximize the expected utility associated to some functional in which the investigator is interested. In this work we made a characterization of the optimal designs obtained from two utility functions associated to an optimal bayesian criterion (Bayes D-optimality) to obtain optimal parameter estimates for two nonlinear models: 1) one-compartment model with absorption and elimination rate, 2) two-compartment model with absorption and elimination rates reversible for the second compartment, both models under normality assumption for the errors. The cited characterization was done via simulation and using diﬀerential evolution to maximize the utility.